2010
DOI: 10.1007/s00125-010-1972-9
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α acutely upregulates amylin expression in murine pancreatic beta cells

Abstract: Aims/hypothesis Amylin, a secretory protein mainly produced by pancreatic beta cells, is elevated in the circulation of patients with diseases related to acute and chronic inflammation, including acute pancreatitis, pancreas graft rejection, obesity and insulin resistance. TNF-α is involved in these disorders. We investigated the effect of TNF-α on amylin levels and the underlying mechanisms, using murine pancreatic beta cell line MIN6 and pancreatic islets. Methods Amylin, proinsulin and prohormone convertase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
4

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 47 publications
(51 reference statements)
0
15
0
4
Order By: Relevance
“…Phillips et al [39] and others have reported various mechanisms by which amylin may be involved in the pathogenesis of AP including stimulation of acinar cell secretion [40] and reduction of pancreatic blood flow [41]. Furthermore, it has been recently demonstrated that TNF-a can acutely upregulates amylin expression in murine pancreatic beta cells [42].…”
Section: Amylinmentioning
confidence: 97%
“…Phillips et al [39] and others have reported various mechanisms by which amylin may be involved in the pathogenesis of AP including stimulation of acinar cell secretion [40] and reduction of pancreatic blood flow [41]. Furthermore, it has been recently demonstrated that TNF-a can acutely upregulates amylin expression in murine pancreatic beta cells [42].…”
Section: Amylinmentioning
confidence: 97%
“…There is a substantial number of reports on direct effects of TNFa inhibiting insulin secretion (for example Kim et al (2008)), and one study (Cai et al 2011b) reported that TNFa induces the expression of amylin from the b-cell. This latter study is of particular relevance in diabetes as the authors also report that there was no concurrent induction of proinsulin expression by TNFa.…”
Section: Tumour Necrosis Factor Amentioning
confidence: 99%
“…Interestingly, IL-1 blockade with the IL-1 receptor antagonist Anakinra was recently shown to inhibit amyloid-associated islet graft injury [36 & ]. The inflammatory cytokine TNF-a also can enhance amylin expression in mouse islets, providing additional evidence that inflammation may promote islet dysfunction through this pathway [45]. Consistent with these findings, a recent study shows that blocking IL-1 and TNF can improve the engraftment of human islets in immune-deficient mice [35 & ].…”
Section: The Barrier Of Chronic Inflammatory Islet Injury: a Role Formentioning
confidence: 75%